Cyclic bridged dicyclopentadienyl catalyst and preparation method and application thereof
By developing a cyclic bridged dicero catalyst, the problems of poor thermal stability of existing catalysts and low comonomer insertion rate at high temperatures are solved, and high activity and high molecular weight polymer preparation is achieved, and the performance of polyolefin materials is improved.
Patent Information
- Application Number
- CN202411694100.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing polyolefin catalysts have poor thermal stability at high temperatures and the comonomer insertion rate is not high, making it difficult to meet the demand of polyolefin materials in the high-temperature solution olefin polymerization process.
A cyclic bridged dicecroleum catalyst was developed, with high thermal stability in structure and regulated catalytic performance by changing the introduced heteroatom species to improve the comonomer insertion rate.
The high activity and thermal stability of the catalyst at high temperatures are achieved, the molecular weight and comonomer insertion rate of copolymerization reaction between ethylene and α-olefins are improved, and the performance of polyolefin polymer materials is enhanced.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal catalysts, and in particular to a cyclic bridged dicyclopentadienyl catalyst and a preparation method and application thereof. Background Art
[0002] Polyolefin materials are currently the most widely used synthetic polymer materials. They have many advantages such as high cost performance, good mechanical properties, and stable thermal properties. They are widely used in various fields of industrial production and daily life, improving and enhancing people's quality of life.
[0003] At present, the preparation of polyolefins mostly adopts high-temperature solution olefin polymerization process. A catalyst is required in the polymerization process. The catalyst used needs to have thermal stability at high temperature, high activity, high molecular weight capacity and copolymerization monomer binding ability.
[0004] Therefore, the development of homogeneous metal catalysts with improved high temperature performance is of great significance for high temperature solution olefin polymerization processes.
[0005] The bridged metallocene catalyst developed by introducing carbon bridge, silicon bridge, heterobridge and other bridge chain structures, because the introduction of bridge group inhibits the rotation of ring structure, increases the stereo rigidity of catalyst and improves the stability of polymer chain growth. The bridged dimethyl carbon bridged metallocene catalyst developed by Mitsui Chemicals has small steric hindrance and rigidity on the bridge and poor thermal stability (CN1684968A). The bridged dimethyl carbon bridged metallocene catalyst developed by ExxonMobil, which introduces alkyl chain on the bridge group, can improve the solubility of catalyst in alkane, but the two aromatic groups and the bridged carbon can be twisted, resulting in a larger fluctuation range of the angle between the two metallocene rings and a larger stereo steric hindrance around the metal center, which is not conducive to the insertion of comonomers with larger volume. In the copolymerization of ethylene and 1-octene, the mass insertion rate of octene is less than 17% (CN1138796C). Herrmann et al. (Chem. Rev., 2000, 100 (4): 1347-1376.) studied the complexes of various bridge groups and their catalytic performance. However, there are few reports on catalysts with cyclic bridged structures. The development of photovoltaics has driven the growing demand for polyolefin elastomers. Many domestic companies have also begun to tackle POE technology. The localization process of POE is advancing rapidly. The problem of lack of catalysts with independent intellectual property rights needs to be solved urgently. Therefore, it is of great significance to innovatively introduce cyclic bridged structures to develop cyclic bridged dicyclopentadiene catalysts, which is conducive to breaking the blockade of foreign patents and obtaining catalyst systems with independent intellectual property rights! Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a cyclic bridged dicyclopentadiene catalyst and a preparation method and application thereof, wherein the cyclic bridged dicyclopentadiene catalyst has high thermal stability.
[0007] To achieve the above object, the present invention provides a cyclic bridged dicyclopentadiene catalyst having a structure shown in Formula I:
[0008]
[0009] wherein M is selected from the fourth subgroup transition metal;
[0010] R1 is selected from halogen, substituted or unsubstituted alkyl, amine; R1 can also be an anionic ligand or a neutral ligand that can coordinate with an isolated electron pair;
[0011] X is selected from oxygen, sulfur, nitrogen, selenium, and carbon;
[0012] When X is selected from oxygen, sulfur or selenium, R2 is absent;
[0013] When X is selected from nitrogen or carbon, R2 is selected from hydrogen, substituted or unsubstituted alkyl, cycloalkyl, aryl, heteroaryl, silicon;
[0014] In the present invention, when X is a carbon atom, it may be connected to one or two R2, and when one R2 is connected, the carbon atom is CH.
[0015] R3~R 22 are independently selected from halogen, hydrogen, substituted or unsubstituted alkyl, alkoxy, cycloalkyl, aryl, heteroaryl, silicon; and R3 to R 22 Can be the same or different;
[0016] Or the R7-R 10 For any two adjacent 11 -R 14 For any two adjacent 16 -R 19 For any two adjacent 20 , R 21 , R 22 , R 15 Any two adjacent substituents in the benzene ring can form a substituted or unsubstituted five-membered to twelve-membered cyclic structure group together with the connected aromatic carbon atom, that is, any adjacent substituents on the benzene ring can be connected by an alkyl chain to form a substituted or unsubstituted five-membered to twelve-membered cyclic structure group.
[0017] The M is a metal element of the catalyst, preferably a fourth subgroup transition metal, more preferably zirconium (Zr), hafnium (Hf) or titanium (Ti).
[0018] The R1 is selected from halogen, substituted or unsubstituted alkyl, amine; preferably halogen, substituted or unsubstituted C1-C10 alkyl, amine; more preferably halogen, substituted or unsubstituted C1-C6 alkyl, amine.
[0019] The substituent of R1 is preferably halogen, alkyl, alkoxy, silicon, aryl or heteroaryl; more preferably halogen, C1-C10 alkyl, C1-C10 alkoxy, C1-C10 alkylsilyl, C6-C12 aryl, C2-C12 heteroaryl; further preferably halogen, C1-C6 alkyl, C1-C6 alkoxy, C1-C6 alkylsilyl, C6-C12 monocyclic or bicyclic aryl, C2-C12 monocyclic or bicyclic heteroaryl; the heteroaryl has 1 to 3 heteroatoms; the heteroaryl has one or more heteroatoms selected from N, O and S. In some specific embodiments of the present invention, the substituent of R1 is specifically one or more of F, Cl, Br, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, methoxy, ethoxy, n-propoxy, isopropoxy, trimethylsilyl and phenyl.
[0020] In some specific embodiments of the present invention, R1 is selected from the following groups: Cl, Br, F, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, benzyl, trimethylsilylmethyl, and bis(trimethylsilyl)amine.
[0021] The X is selected from oxygen, sulfur, nitrogen, selenium and carbon.
[0022] When X is selected from oxygen, sulfur or selenium, R2 is absent.
[0023] When X is selected from nitrogen or carbon, R2 is selected from hydrogen, substituted or unsubstituted alkyl, cycloalkyl, aryl, heteroaryl, silicon; preferably hydrogen, substituted or unsubstituted C1-C10 alkyl, 3-6 membered cycloalkyl, C6-C12 aryl, C2-C12 heteroaryl, silicon; further preferably hydrogen, substituted or unsubstituted C1-C8 alkyl, C6-C12 monocyclic or bicyclic aryl, C2-C12 monocyclic or bicyclic heteroaryl, silicon; the heteroaryl has 1 to 3 heteroatoms; the heteroaryl has one or more heteroatoms selected from N, O, S.
[0024] The substituent of R2 is preferably halogen, alkyl, alkoxy, aryl or heteroaryl; more preferably halogen, C1-C10 alkyl, C1-C10 alkoxy, C6-C12 aryl, C2-C12 heteroaryl; further preferably halogen, C1-C8 alkyl, C1-C8 alkoxy, C6-C12 monocyclic or bicyclic aryl, C2-C12 monocyclic or bicyclic heteroaryl; the heteroaryl has 1 to 3 heteroatoms; the heteroaryl has one or more heteroatoms selected from N, O and S. In some specific embodiments of the present invention, the substituent of R2 is specifically one or more of F, Cl, Br, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, methoxy, ethoxy, n-propoxy, isopropoxy and phenyl.
[0025] In some specific embodiments of the present invention, R2 is specifically selected from H, Cl, Br, F, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, C9 alkyl, C10 alkyl, cyclopentyl, cyclohexyl, phenyl, benzyl, p-methylphenyl, p-methoxyphenyl, 3,5-di-tert-butylphenyl, trimethylsilyl, triphenylsilyl.
[0026] R3~R 22 Independently selected from halogen, hydrogen, substituted or unsubstituted alkyl, alkoxy, cycloalkyl, aryl, heteroaryl, silicon; preferably halogen, hydrogen, substituted or unsubstituted C1-C20 alkyl, C1-C20 alkoxy, 3-6 membered cycloalkyl, C6-C12 aryl, C2-C12 heteroaryl, silicon; more preferably halogen, hydrogen, substituted or unsubstituted C1-C6 alkyl, C1-C6 alkoxy, 5-6 membered cycloalkyl, C6-C12 monocyclic or bicyclic aryl, C2-C12 monocyclic or bicyclic heteroaryl, silicon; the heteroaryl has 1 to 3 heteroatoms; the heteroaryl has one or more heteroatoms selected from N, O, S.
[0027] R3~R 22 The substituents of are independently selected from halogen, alkyl, alkoxy, aryl or heteroaryl; more preferably halogen, C1-C10 alkyl, C1-C10 alkoxy, C6-C12 aryl, C2-C12 heteroaryl; further preferably halogen, C1-C6 alkyl, C6-C12 monocyclic or bicyclic aryl, C2-C12 monocyclic or bicyclic heteroaryl; the heteroaryl has 1 to 3 heteroatoms; the heteroaryl has one or more heteroatoms selected from N, O, S. In some specific embodiments of the present invention, R3-R 22 The substituents are specifically one or more of F, Cl, Br, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, methoxy, ethoxy, n-propoxy, isopropoxy, and phenyl.
[0028] In some specific embodiments of the present invention, the R3 to R 22 Specifically selected from one or more of F, Cl, Br, I, hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, C9 alkyl, C10 alkyl, methoxy, ethoxy, n-propoxy, isopropoxy, phenyl, benzyl, p-methylphenyl, p-methoxyphenyl, pentafluorophenyl, 3,5-di-tert-butylphenyl, trimethylsilyl, triphenylsilyl, and trifluoromethyl.
[0029] Preferably, the R3 to R 22Any three or more of them are selected from alkyl groups or silicon groups, more preferably C1 to C20 alkyl groups or silicon groups.
[0030] Preferably, R8, R9, R 12 , R 13 , R 17 , R 18 , R 21 , R 22 Any one or more of them are selected from alkyl groups or silicon groups, more preferably C1-C20 alkyl groups or silicon groups.
[0031] Preferably, R7~R 22 They may or may not be hydrogen at the same time.
[0032] Preferably, R3, R4, R5, and R6 are all hydrogen atoms, or 1 to 2 of them are not hydrogen atoms.
[0033] Or the R7-R 10 For any two adjacent 11 -R 14 For any two adjacent 16 -R 19 For any two adjacent 20 , R 21 , R 22 , R 15 Any two adjacent substituents in the benzene ring can form a substituted or unsubstituted five-membered to twelve-membered cyclic structure group together with the connected aromatic carbon atom, that is, any adjacent substituents on the benzene ring can be connected by an alkyl chain to form a substituted or unsubstituted five-membered to twelve-membered cyclic structure group.
[0034] Preferably, the R7-R 10 For any two adjacent 11 -R 14 For any two adjacent 16 -R 19 For any two adjacent 15 , R 20 -R 22 Any two adjacent ones of the aryl carbon atoms to which they are connected together form a substituted or unsubstituted five-membered to eight-membered cyclic structure group.
[0035] More preferably, the R7-R 10 For any two adjacent 11 -R 14 For any two adjacent 16 -R 19 For any two adjacent 15 , R 20 -R22 Any two adjacent ones of the aryl carbon atoms to which they are connected together form a substituted or unsubstituted five-membered to six-membered cyclic structure group.
[0036] Preferably, the cyclic structural group is an aromatic group, a heteroaromatic group or a cycloalkyl group, more preferably a substituted or unsubstituted phenyl group, a cyclopentyl group or a cyclohexyl group.
[0037] Preferably, R8 and R9, R 12 and R 13 , R 17 and R 18 , R 21 and R 22 Together with the connected aromatic carbon atom, they respectively form the above-mentioned substituted or unsubstituted cyclic structure group.
[0038] The substituent of the cyclic structural group is preferably halogen, alkyl, alkoxy, aryl or heteroaryl; more preferably halogen, C1-C10 alkyl, C1-C10 alkoxy, C6-C12 aryl, C2-C12 heteroaryl; further preferably halogen, C1-C6 alkyl, C6-C12 monocyclic or bicyclic aryl, C2-C12 monocyclic or bicyclic heteroaryl; the heteroaryl has 1 to 3 heteroatoms; the heteroaryl has one or more heteroatoms selected from N, O, and S. In some specific embodiments of the present invention, the substituent of the cyclic structural group is specifically one or more of F, Cl, Br, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, methoxy, ethoxy, n-propoxy, isopropoxy, and phenyl.
[0039] In some specific embodiments of the present invention, the cyclic structural group is a cyclopentyl or cyclohexyl substituted with a methyl group.
[0040] In some specific embodiments of the present invention, the R7-R 10 For any two adjacent 11 -R 14 For any two adjacent 16 -R 19 For any two adjacent 15 , R 20 -R 22 Any two adjacent ones, preferably R8 and R9, R 12 and R 13 , R 17 and R 18 , R 21 and R 22 , respectively, together with the connected phenyl group, form any of the following groups:
[0041]
[0042] Preferably, the cyclic bridged dicyclopentadiene catalyst has any of the following structures:
[0043]
[0044]
[0045] The present invention also provides a method for preparing the above-mentioned cyclic bridged dicyclopentadienyl catalyst, comprising the following steps:
[0046] S1) reacting the compound represented by formula a with the compound represented by formula b to obtain a compound represented by formula c;
[0047] S2) the compound represented by formula c undergoes coordination reaction with a metal precursor to obtain a cyclic bridged dicyclopentadienyl catalyst represented by formula I;
[0048]
[0049] Among them, M, R1, X, R2, R3~R 22 The scope is the same as above and will not be repeated here.
[0050] The step S2) is preferably as follows:
[0051] In a nitrogen atmosphere, a lithium salt solution of a monolithium salt Lli (compound shown in formula c) treated with an amount of n-butyl lithium is reacted with MX4, and then treated with an excess of methyl lithium to obtain a cyclic bridged diocene catalyst shown in formula I.
[0052] Wherein, X is a halogen.
[0053] The step S2) is more preferably as follows:
[0054] Under a nitrogen atmosphere, 1 molar equivalent of the compound represented by the ligand formula c and 4 molar equivalents of LiMe are reacted in THF at reflux at low temperature (preferably -35°C), preferably for 6 hours. Under low temperature (preferably -35°C), the above-mentioned ligand lithium salt is added to the zirconium chloride solution, restored to room temperature and stirred, preferably for 6 hours, the solvent is drained, and washed with 5 mL of anhydrous n-hexane for several times. After the solvent is drained from the filter residue, a good solvent is added to dissolve and filter, the solvent is removed from the good solvent filtrate, and then a poor solvent is added to wash to obtain the cyclobridged dicyclopentadiene catalyst.
[0055] The good solvent is preferably one or more of dichloromethane, toluene and THF.
[0056] The poor solvent is preferably one or more of n-hexane and diethyl ether.
[0057] Optionally, the compound represented by formula a is prepared by reacting a compound represented by formula a-1 and a compound represented by formula a-2;
[0058]
[0059] Preferably, the preparation method of the compound represented by formula a is as follows:
[0060] In a nitrogen atmosphere, the compound represented by formula a-2 is dissolved in an ethanol solution containing 1 equivalent of sodium ethoxide, and 1.2 equivalents of the compound represented by formula a-1 are added dropwise at 50°C. After the addition is completed, the mixture is returned to room temperature and stirred, preferably for 12 hours, filtered, and the solid is washed with 20 mL of cold ethanol, and then recrystallized with 80 mL of methanol to obtain an orange-red solid, which is then washed once with 10 mL of cold methanol. The solid is vacuum dried to obtain the compound represented by formula a.
[0061] The equation for the reaction is as follows:
[0062]
[0063] The present invention also provides the use of the above-mentioned bridged diocene catalyst as an olefin polymerization catalyst.
[0064] The polymerization may be homopolymerization or copolymerization.
[0065] The present invention also provides a catalyst system for olefin polymerization, comprising at least two of a catalyst, a co-catalyst, and a boron agent;
[0066] The catalyst is the above-mentioned cyclic bridged dicyclopentadiene catalyst.
[0067] The co-catalyst is preferably one or more of alkylaluminum, aluminoxane and alkylaluminum chloride; more preferably one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane, modified methylaluminoxane (MMAO), etc.
[0068] The boron agent is preferably a highly soluble oil boron, more preferably trispentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl) borate, tris(4-octylphenyl)carbonium tetrakis(pentafluorophenyl) borate, [PhNHMe2][B(C6F5)4], [(C 18 H 37 )2NHMe][B(C6F5)4], [PhNHMe2][B(C6F5)4], [(C 18 H 37 )2NHMe][B(C6F5)4]、[C 18 H 37 NHMePh][B(C6F5)4], etc.
[0069] The olefin may be an olefin that can undergo olefin polymerization reaction and is well known to those skilled in the art, and is preferably one or more of ethylene, propylene, 1-butene, 1-hexene, 1-octene, styrene, cyclopentene, cyclohexene, norbornene, ethylidene norbornene, 1,3-butadiene, 1,3-pentadiene, and the like.
[0070] The present invention also provides a method for preparing an olefin polymer, comprising the following steps:
[0071] Under the catalytic action of the above-mentioned cyclic bridged dioctylene catalyst or the above-mentioned catalyst system for olefin polymerization, one or more olefins are polymerized to prepare olefin polymers.
[0072] In the present invention, the polymerization reaction temperature is preferably 80-200° C., the polymerization reaction time is preferably 10-20 min, and the polymerization reaction pressure is preferably 0.1-10.0 MPa, more preferably 0.5-9.5 MPa.
[0073] The molar ratio of the aluminum atoms in the co-catalyst to the metal atoms in the catalyst is preferably (5-5000):1, more preferably (100-1500):1.
[0074] Preferably, an alkane solvent is added as a diluent during the polymerization reaction, and the alkane solvent is preferably one or more of organic solvents such as n-hexane, isooctane, ISOPAR E, cyclohexane, heptane, toluene, etc.
[0075] The olefin may be an olefin that can undergo olefin polymerization reaction and is well known to those skilled in the art, and is preferably one or more of ethylene, propylene, 1-butene, 1-hexene, 1-octene, styrene, cyclopentene, cyclohexene, norbornene, ethylidene norbornene, 1,3-butadiene, 1,3-pentadiene, and the like.
[0076] When one olefin is used for the polymerization reaction, the polymerization reaction is a homopolymerization reaction, and the obtained olefin polymer is a homopolymer.
[0077] When a plurality of olefins are used for polymerization, the polymerization reaction is a copolymerization reaction, and the obtained olefin polymer is a copolymer.
[0078] Specifically, the present invention provides a binary copolymer of ethylene and α-olefin, wherein the molecular weight Mw of the copolymer is 100 to 1000 kg·mol -1 , the molar insertion rate is 7 to 40 mol%, the melting point is 20 to 90°C, the glass transition temperature is -30 to -90°C, and the transmittance is ≥91%.
[0079] The α-olefin is preferably one or more of propylene, 1-butene, 1-hexene, 1-octene, and styrene.
[0080] Specifically, the present invention provides a terpolymer of ethylene, α-olefin and diene, wherein the molecular weight Mw of the terpolymer is 100 to 1000 kg·mol -1 , molar insertion rate is 9 to 40 mol%, melting point is 25 to 95°C, glass transition temperature is -25 to -95°C, and light transmittance is ≥91%.
[0081] The diene is preferably one or more of ethylidene norbornene, 1,3-butadiene, and 1,3-pentadiene.
[0082] The experimental results show that the molecular weight of the polymer obtained by copolymerizing ethylene and 1-butene catalyzed by the cyclic bridged dicyclopentadiene catalyst provided by the present invention is as high as 38.5×10 4 g / mol, the highest molar insertion rate of 1-butene is 36.2%; the molecular weight of the polymer obtained by copolymerization of ethylene and 1-hexene is up to 40.1×10 4 g / mol, the highest molar insertion rate of 1-hexene is 25.1%; the molecular weight of the polymer obtained by copolymerization of ethylene and 1-octene is up to 36.1×10 4 g / mol, and the molar insertion rate of 1-octene was the highest at 19.0%.
[0083] Compared with the prior art, the present invention provides a cyclic bridged dicyclopentadiene catalyst having a structure shown in formula I.
[0084] The cyclic bridged dicyclopentadiene catalyst provided by the present invention has high catalytic activity, good high temperature resistance and good copolymerization activity. Compared with the prior art, its structure is easy to modify, and it can be used to catalyze the copolymerization reaction of ethylene and alpha-olefins such as 1-butene, 1-hexene and 1-octene to obtain a polymer product with high molecular weight and high comonomer insertion rate, which is helpful to enhance the competitiveness of my country's polyolefin polymer material technology market.
[0085] The present invention innovatively introduces a cyclic bridging structure on the bridge of the bridged dicyclopentadienyl catalyst, designs and synthesizes a new type of cyclic bridged dicyclopentadienyl catalyst, and by changing the type of heteroatoms introduced, the electronic effect of the model metal catalyst can be easily regulated, thereby achieving different catalytic properties, and preparing polyolefin polymer materials with various structures and various properties. The above-mentioned cyclic bridging structure not only maintains the overall rigidity of the catalyst molecule and maintains high temperature resistance, but also controls the two substituents on the bridge on a plane, and the steric hindrance is relatively small, and it is expected to obtain a higher comonomer insertion ability. The two unlinked aromatic groups are relatively volatile and have relatively large steric hindrance, which may be unfavorable for the insertion of comonomers. Although the increase in rigidity improves thermal stability, it also reduces the comonomer insertion ability. The present application links the introduced rigid structure to a plane, which can reduce the position of the three-dimensional space, and achieves the simultaneous improvement of thermal stability and comonomer insertion ability.
[0086] In addition, the present invention adopts a strategy of synthesizing large sterically hindered fulvene and attacking small sterically hindered cyclopentadienyl, which makes the synthesis of the catalyst simpler and easier, and improves the synthesis efficiency.
[0087] The novel cyclic bridged dicyclopentadienyl catalyst provided by the present invention has the characteristics of cheap and readily available raw materials, simple synthesis route and high product yield. In the presence of an appropriate amount of promoter, such as MAO, zirconium and hafnium metal catalysts show extremely high activity, which can reach 16.08×10 4 g(PE)·g(M), the prepared polyethylene has high linearity and high molecular weight, and the prepared ethylene and α-olefin copolymer has good elasticity, controllable insertion rate and good light transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 This is a diagram of a polymer sample obtained in Example 4 of the present invention;
[0089] Figure 2 This is a diagram of a polymer sample obtained in Example 5 of the present invention;
[0090] Figure 3 This is a diagram of a polymer sample obtained in Example 6 of the present invention;
[0091] Figure 4 is the H NMR spectrum of the compound of formula II-1 of the present invention;
[0092] Figure 5 is the H NMR spectrum of the LLi-1 compound of the present invention;
[0093] Figure 6 The hydrogen NMR spectrum of the catalyst I-1 of the present invention. DETAILED DESCRIPTION
[0094] In order to further illustrate the present invention, the cyclic bridged dicyclopentadiene catalyst provided by the present invention and its preparation method and application are described in detail below in conjunction with the examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.
[0095] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0096] Example 1. Preparation of Ligand Monolithium Salt LLi
[0097] The general structural formula of the single lithium salt LLi is as follows:
[0098]
[0099] The preparation process is as follows:
[0100]
[0101] 18 mmol of the compound represented by formula (II) was weighed and dissolved in 100 mL of anhydrous ether. Under a nitrogen atmosphere of -35°C, 18 mmol of cyclopentadienyl lithium represented by formula (III) was added. The mixture was gradually restored to room temperature and stirred for 3 hours before removing the solvent. The remaining solid was slurried with n-hexane (100 mL), filtered, washed with additional n-hexane (2x100 mL), and then dried under vacuum to obtain the ligand monolithium salt LLi.
[0102] The synthesis method of the compound represented by the above formula (II) is as follows:
[0103] Weigh 0.25 mol of sodium ethoxide, add 190 mL of anhydrous ethanol at room temperature, and stir until the sodium ethoxide is completely dissolved to prepare an ethanol solution of sodium ethoxide. Add 0.25 mol of the compound shown in formula (IV) to the sodium ethoxide solution, heat the reaction system to 50°C and stir until it is completely dissolved. Under this temperature condition, add 0.3 mol of fluorene shown in formula (V) dropwise to the reaction system, return to room temperature after the addition is completed, stir for 12 hours, filter, wash the solid with 20 mL of cold ethanol, and then recrystallize with 80 mL of methanol to obtain an orange-red solid, wash it once with 10 mL of cold methanol, and vacuum dry the solid to obtain the compound shown in formula (II).
[0104] The cyclopentadienyl lithium represented by the above formula (III) is prepared by reacting substituted cyclopentadiene with n-butyl lithium.
[0105] The following compounds were prepared according to the above method:
[0106] LLi1: R3~R 22 =Hydrogen; X=O; R2 does not exist;
[0107] LLi2: R3~R 22 = hydrogen; X = S; R2 does not exist;
[0108] LLi3: R2 = methyl; R3 ~ R 22 =Hydrogen; X = N;
[0109] LLi4: R2 = ethyl; R3 ~ R 22 =Hydrogen; X = N;
[0110] LLi5: R2 = tert-butyl; R3 ~ R 22 =Hydrogen; X = N;
[0111] LLi6: R2 = phenyl; R3 ~ R 22 =Hydrogen; X = N;
[0112] LLi7: R3~R7, R 10 , R 11 , R 14~ R 16 , R 18~ R 21 =Hydrogen; R 17 , R 22 = methoxy; R8,
[0113] R9, R 12 , R 13 = tert-butyl; X = O; R2 does not exist;
[0114] LLi8: R3~R7, R 10 , R 11 , R 14~ R 22 =Hydrogen; R8, R9, R 12 , R 13 = tert-butyl; X =
[0115] O; R2 does not exist;
[0116] LLi9: R2 = methyl; R3~R7, R 10 , R 11 , R 14~ R 22 =Hydrogen; R8, R9, R 12 , R 13 =Uncle
[0117] Butyl; X = CMe;
[0118] LLi10: R3~R7, R 10 , R 11 , R 14~ R 22= hydrogen; R8, R9 and the carbon atoms of the benzene ring are connected to form a five-membered ring, R 12 , R 13 Connected to the carbon atom of the benzene ring to form a five-membered ring; X=O; R2 does not exist;
[0119] LLi11: R3~R7, R 10 , R 11 , R 14~ R 17 , R 19 , R 20 , R 22 =Hydrogen; R8, R9, R 12 ,
[0120] R 13 , R 18 , R 21 = tert-butyl; X = O; R2 does not exist;
[0121] LLi12: R3~R7, R 10 , R 11 , R 14~ R 16 , R 18 ~R 21 =Hydrogen; R8, R9, R 12 , R 13 , R 17 ,
[0122] R 22 = tert-butyl; X = O; R2 does not exist;
[0123] LLi13: R3~R7, R 10 ~R 11 , R 14~ R 16 , R 19 ~R 20 =Hydrogen; R8, R9, R 12 , R 13 = Tert-Butyl
[0124] Base; R 17 , R 18 The carbon atom of the benzene ring is fused to form tetramethylcyclohexyl; R 21 , R 22 The carbon atom of the benzene ring is fused to form tetramethylcyclohexyl; X=O; R2 does not exist;
[0125] LLi14: R3~R7, R 10 ~R 11 , R 14~ R 16 , R 19 ~R 20= hydrogen; R8, R9 and the carbon atoms of the benzene ring are combined to form a tetramethylcyclohexyl group; R 12 , R 13 The carbon atom of the benzene ring is fused to form tetramethylcyclohexyl; R 17 , R 18 The carbon atom of the benzene ring is fused to form tetramethylcyclohexyl; R 21 , R 22 The carbon atom of the benzene ring is fused to form tetramethylcyclohexyl; X=O; R2 does not exist.
[0126] LLi15: R3~R7, R 10 ~R 11 , R 14~ R 16 , R 18 ~R 21 = hydrogen; R8, R9 and the carbon atoms of the benzene ring are combined to form a tetramethylcyclohexyl group; R 12 , R 13 The carbon atom of the benzene ring is fused to form tetramethylcyclohexyl; R 17 , R 22 isopropyl; X=O; R2 does not exist.
[0127] Figure 4 is the H NMR spectrum of the compound of formula II-1 of the present invention; in formula II-1, R7 to R 22 =Hydrogen; X=O.
[0128] Figure 5 The figure is the hydrogen NMR spectrum of the LLi-1 compound of the present invention.
[0129] Example 2: Preparation of Cyclobridged Dicyclopentadiene Catalyst
[0130] In the following preparation process, the type of M is consistent with that in the catalyst structure formula.
[0131] (1) Preparation of Catalysts I-1 to I-16
[0132] Under nitrogen atmosphere, weigh 3.9mmol of ligand monolithium salt (one of LLi1~LLi14) and add 40mL of ether to form slurry. At -35℃, add 16mmol of LiMe dropwise, gradually return to room temperature and stir for 3h. Then weigh 3.9mmol of MCl4 and add 20mL of ether at -35℃. Slowly add the above ligand monolithium salt solution to the MCl4 solution, return to room temperature and stir for 6h. Drain the reaction reagents and extract the product with n-hexane to remove LiCl. Recrystallize the product with toluene / n-hexane (volume ratio of 1:16) to obtain a metal complex.
[0133] (2) Preparation of Catalyst I-17
[0134] Under nitrogen atmosphere, 3.9 mmol of ligand LLi14 was weighed and added to 40 mL of ether to form a slurry. At -35 °C, the mixture was added dropwise. n 3.9mmol BuLi, gradually return to room temperature and stir for 3h, then weigh 3.9mmol MCl4, add 20mL ether at -35℃, slowly add the above ligand lithium salt solution to the MCl4 solution, return to room temperature and stir for 6h, drain the reaction reagents, extract the product with dichloromethane (toluene) to remove LiCl. Recrystallize the product with dichloromethane / n-hexane (volume ratio of 1:16) to obtain a metal complex.
[0135] (3) Preparation of Catalyst I-18
[0136] Under nitrogen conditions, the metal catalyst I-17 (3 mmol) prepared above was dissolved in toluene (50 mL), cooled to -35 °C, benzylmagnesium bromide solution (6 mmol) was slowly added dropwise, and the mixture was returned to room temperature for 3 h. The insoluble matter was filtered out, and the filtrate was drained to obtain the target metal complex I-18.
[0137] The experimental results are as follows:
[0138] Catalyst I-1, output: 0.73 g, yield: 35.1%, purity 95%, elemental analysis: measured (calculated) C: 74.79 (74.81); H: 4.93 (4.95); O: 3.19 (3.02);
[0139] Catalyst I-2, yield: 0.72 g, yield: 33.6%, purity 94%, elemental analysis: measured (calculated) C: 72.60 (72.61); H: 4.81 (4.80); S: 5.85 (5.87);
[0140] Catalyst I-3, output: 0.68 g, yield: 32.7%, purity 96%, elemental analysis: measured (calculated) C: 75.23 (75.21); H: 5.39 (5.37); N: 2.57 (2.58);
[0141] Catalyst I-4, yield: 0.75 g, yield: 34.5%, purity 95%, elemental analysis: measured (calculated) C: 75.48 (75.49); H: 5.60 (5.61); N: 2.53 (2.52);
[0142] Catalyst I-5, yield: 0.73 g, yield: 32.1%, purity 94%, elemental analysis: measured (calculated) C: 75.97 (75.98); H: 6.04 (6.03); N: 2.38 (2.39);
[0143] Catalyst I-6, yield: 0.79 g, yield: 33.5%, purity 97%, elemental analysis: measured (calculated) C: 77.43 (77.44); H: 5.19 (5.17); N: 2.31 (2.32);
[0144] Catalyst I-7, yield: 1.01 g, yield: 31.7%, purity 95%, elemental analysis: measured (calculated) C: 75.22 (75.23); H: 7.69 (7.68); O: 5.88 (5.89);
[0145] Catalyst I-8, output: 1.00 g, yield: 33.9%, purity 96%, elemental analysis: measured (calculated) C: 78.02 (78.03); H: 7.74 (7.75); O: 2.13 (2.12);
[0146] Catalyst I-9, output: 1.04 g, yield: 31.8%, purity 94%, elemental analysis: measured (calculated) C: 69.93 (69.94); H: 6.94 (6.95); O: 1.91 (1.90);
[0147] Catalyst I-10, output: 0.90 g, yield: 32.4%, purity 95%, elemental analysis: measured (calculated) C: 82.78 (82.79); H: 8.23 (8.22); O: 2.24 (2.25);
[0148] Catalyst I-11, output: 1.01 g, yield: 33.2%, purity 94%, elemental analysis: measured (calculated) C: 80.04 (80.04); H: 8.27 (8.27);
[0149] Catalyst I-12, output: 0.77 g, yield: 32.5%, purity 93%, elemental analysis: measured (calculated) C: 76.79 (76.80); H: 5.61 (5.62); O: 2.61 (2.62);
[0150] Catalyst I-13, output: 1.12 g, yield: 33.1%, purity 94%, elemental analysis: measured (calculated) C: 79.01 (79.02); H: 8.59 (8.61); O: 1.84 (1.85);
[0151] Catalyst I-14, output: 1.10 g, yield: 32.6%, purity 95%, elemental analysis: measured (calculated) C: 79.00 (79.02); H: 8.60 (8.61); O: 1.83 (1.85);
[0152] Catalyst I-15, output: 1.20 g, yield: 31.5%, purity 96%, elemental analysis: measured (calculated) C: 80.08 (80.10); H: 8.88 (8.89); O: 1.63 (1.64);
[0153] Catalyst I-16, output: 1.03 g, yield: 31.6%, purity 97%, elemental analysis: measured (calculated) C: 79.17 (79.18); H: 7.96 (7.97); O: 1.91 (1.92);
[0154] Catalyst I-17, yield: 1.12 g, yield: 32.7%, purity 94%, elemental analysis: measured (calculated) C: 72.73 (72.74); H: 6.90 (6.91); O: 1.82 (1.83);
[0155] Catalyst I-18, output: 1.01 g, yield: 34.1%, purity 95%, elemental analysis: measured (calculated) C: 81.56 (81.57); H: 7.55 (7.56); O: 1.61 (1.62).
[0156] Figure 6 The hydrogen NMR spectrum of the catalyst I-1 of the present invention.
[0157] Example 3: Catalytic Ethylene Polymerization
[0158] The polymerization reaction was carried out in a 1000mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was heated to 160°C, vacuumed for 2h, and ethylene was replaced three times. The system was cooled to 65°C. Under vacuum conditions, the required solvent and co-catalyst modified methylaluminoxane (MMAO) were added to the polymerization autoclave in sequence. The temperature in the autoclave was raised to the polymerization temperature of 150°C. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 4MPa. The balance was 15min to fully dissolve ethylene to saturation (total liquid volume 600mL). Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using a 4.5MPa ethylene pressure difference. The timing was started and the reaction was terminated after 15min of reaction. The temperature was quickly cooled to 60°C, and the reactor was opened after the pressure was released. The reaction mixture was poured into a mixed solution of 2M hydrochloric acid and ethanol with a volume ratio of 1:1. After stirring for 30min, it was filtered and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high temperature GPC. The comonomer insertion rate was analyzed by high temperature quantitative carbon spectrum. The results are shown in Table 1.
[0159] Table 1 Data of ethylene polymerization catalyzed by catalysts I-1 to I-18 as main catalysts a
[0160]
[0161] aPolymerization conditions: the dosage of the main catalyst I-1~I-18 is 1μmol, the co-catalyst is MMAO-7, Al / M=500, the polymerization temperature: 150℃, the polymerization pressure is 4.5MPa, and the polymerization time is 15min; bMolecular weight and molecular weight distribution are measured by GPC.
[0162] Example 4: Catalytic copolymerization of ethylene and 1-butene
[0163] The polymerization reaction was carried out in a 1000 mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was heated to 160° C. and vacuumed for 2 h. The system was cooled to 65° C. The required solvent and the designed amount of 1-butene (for convenience of calculation, the polymerization data 1-butene in Table 2 was converted into the molar concentration relative to the n-hexane solvent) were added to the polymerization autoclave in sequence, and the required amount of co-catalyst (the final total volume of the solution was 600 mL) was added. The temperature in the autoclave was raised to the polymerization temperature of 150° C. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 4 MPa. The temperature was balanced for 15 min to fully dissolve ethylene to saturation. Under a nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (4.5 MPa). The timing was started and the reaction was terminated after 15 min of reaction. First, the temperature was rapidly lowered to 60°C, and after the pressure was released, the reactor was opened, and the reaction mixture was poured into a mixed solution of 2M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 30 minutes, filtered, and the polymer product was dried in a vacuum oven. The mass was weighed, and the polymer molecular weight and molecular weight distribution were analyzed by high-temperature GPC, and the comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 2.
[0164] Table 2 Data of ethylene and 1-butene copolymerization catalyzed by catalysts I-1 to I-18 as main catalysts a
[0165]
[0166]
[0167] aPolymerization conditions: the dosage of main catalyst I-1~I-18 is 1μmol, the co-catalyst is MMAO-7, Al / M=500, the polymerization temperature is 150℃, the polymerization pressure is 4.5MPa, and the polymerization time is 15min; bMolecular weight and molecular weight distribution are measured by GPC; c 13CNMR measured that the d co-catalyst was MMAO-3A, Al / M=500; the e co-catalyst was tripentafluorophenyl boron, MMAO-3A, B / M=1.2, Al / M=100; the f co-catalyst was triphenylcarbonium tetrakis(pentafluorophenyl)borate, triisobutylaluminum, B / M=1.2, Al / M=100; the g co-catalyst was [PhNHMe2][B(C6F5)4], tri-n-octylaluminum, B / M=1.2, Al / M=100; the h co-catalyst was [(C18H37)2NHMe][B(C6F5)4], tri-n-octylaluminum, B / M=1.2, Al / M=100.
[0168] Figure 1 This is a picture of the polymer sample prepared in this embodiment. It can be seen that the obtained polymer has good transparency and uniformity, good light transmittance, and high insertion rate, and is an elastomeric material.
[0169] Example 5: Catalytic copolymerization of ethylene and 1-hexene
[0170] The polymerization reaction was carried out in a 1000 mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was heated to 160° C. and vacuumed for 2 h. The system was cooled to 65° C. The required solvent and the designed amount of 1-hexene (for convenience of calculation, the polymerization data 1-hexene in Table 3 was converted into the molar concentration relative to the normal hexane solvent) were added to the polymerization autoclave in sequence, and the required amount of modified methylaluminoxane (MMAO) was added (the final total volume of the solution was 600 mL). The temperature in the autoclave was raised to the polymerization temperature of 150° C. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 4 MPa. The temperature was balanced for 15 min to fully dissolve ethylene to saturation. Under a nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (4.5 MPa). The timing was started and the reaction was terminated after 15 min of reaction. First, the temperature was rapidly lowered to 60°C, and after the pressure was released, the reactor was opened, and the reaction mixture was poured into a mixed solution of 2M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 30 minutes, filtered, and the polymer product was dried in a vacuum oven. The mass was weighed, and the molecular weight and molecular weight distribution of the polymer were analyzed by high-temperature GPC, and the comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 3.
[0171] Table 3 Data of copolymerization of ethylene and 1-hexene catalyzed by catalysts I-1 to I-18 as main catalysts
[0172]
[0173]
[0174] aPolymerization conditions: the dosage of main catalyst I-1~I-18 is 1μmol, the co-catalyst is MMAO-7, Al / M=500, the polymerization temperature is 150℃, the polymerization pressure is 4.5MPa, and the polymerization time is 15min; bMolecular weight and molecular weight distribution are measured by GPC; c 13 Measured by CNMR.
[0175] Figure 2 This is a picture of the polymer sample prepared in this example. It can be seen that the polymer has good uniformity, is translucent, and has a good insertion rate.
[0176] Example 6: Catalytic copolymerization of ethylene and 1-octene
[0177] The polymerization reaction was carried out in a 1000mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was heated to 160°C, vacuumed for 2h, and the system was cooled to 35°C. The required 1-octene (making the 1-octene concentration 1.50mol / L) and the designed amount of solvent were added to the polymerization autoclave in sequence, and the required amount of modified methylaluminoxane (MMAO) was added (the final total volume of the solution was 600mL). The temperature in the autoclave was raised to the polymerization temperature of 150°C. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 4MPa. The balance was 15min to fully dissolve ethylene to saturation. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (4.5MPa). The timing was started and the reaction was terminated after 15min of reaction. The temperature was quickly cooled to 60°C, and the reactor was opened after the pressure was released. The reaction mixture was poured into a mixed solution of 2M hydrochloric acid and ethanol with a volume ratio of 1:1, stirred for 30min, filtered, and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high-temperature GPC. The comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 4.
[0178] Table 4 Data of copolymerization of ethylene and 1-octene catalyzed by catalysts I-1 to I-18 as main catalysts
[0179]
[0180]
[0181] aPolymerization conditions: the dosage of main catalyst I-1~I-18 is 1μmol, the co-catalyst is MMAO-7, Al / M=500, the concentration of 1-octene is 1.50mol / L, the polymerization pressure is 3MPa, the polymerization temperature is 90℃, and the polymerization time is 15min; bMolecular weight and molecular weight distribution are measured by GPC; c 13 Measured by CNMR.
[0182] Figure 3This is a picture of the polymer sample prepared in this embodiment. It can be seen that the polymer has good transparency, high light transmittance, good uniformity and high insertion rate.
[0183] Example 7: Preparation of propylene-based elastomer by catalytic copolymerization of ethylene and propylene
[0184] The polymerization reaction was carried out in a 1000mL stainless steel autoclave. The autoclave equipped with mechanical stirring was heated to 160°C, vacuumed for 2h, and the system was cooled to 45°C. The required propylene 200g and the designed amount of solvent were added to the autoclave in turn, and the required amount of modified methylaluminoxane (MMAO) was added (the final total volume of the solution was 600mL). The temperature in the autoclave was raised to the required polymerization temperature of 80°C. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 2.5MPa. Balance for 15min to fully dissolve ethylene to saturation. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (3MPa). The timing was started and the reaction was terminated after 15min of reaction. The temperature was quickly cooled to 60°C, and the reactor was opened after the pressure was released. The reaction mixture was poured into a mixed solution of 2M hydrochloric acid and ethanol with a volume ratio of 1:1, stirred for 30min, filtered, and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high-temperature GPC. The comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 5.
[0185] Table 5 Data of ethylene and propylene copolymerization catalyzed by catalysts I-1 to I-6 as main catalysts
[0186]
[0187] aPolymerization conditions: the dosage of main catalyst I-1~I-6 is 1μmol, the co-catalyst is MMAO-7, Al / M=500, the polymerization pressure is 3MPa, the polymerization temperature is 80℃, and the polymerization time is 15min; bMolecular weight and molecular weight distribution are measured by GPC; c 13 Measured by CNMR.
[0188] Example 8: Preparation of propylene-based elastomer by catalytic copolymerization of propylene / 1-butene
[0189] The polymerization reaction was carried out in a 1000mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was heated to 160°C, vacuumed for 2h, and the system was cooled to 45°C. 200g of propylene and 50g of 1-butene were added to the polymerization autoclave in turn, and the required amount of modified methylaluminoxane (MMAO) (the final total volume of the solution was 600mL) was added. The temperature in the autoclave was raised to the polymerization temperature of 80°C. After the temperature was constant, the polymerization pressure was maintained at 1MPa, and the balance was 15min. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feed tank, and then the main catalyst was pressed into the reaction system using the nitrogen pressure difference (1.2MPa), and the timing was started. The reaction was terminated after 15min of reaction. First, the temperature was quickly cooled to 60°C, and the reactor was opened after the pressure was released. The reaction mixture was poured into a mixed solution of 2M hydrochloric acid and ethanol with a volume ratio of 1:1, stirred for 30min, filtered, and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high-temperature GPC. The comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 6.
[0190] Table 6 Data of propylene / 1-butene copolymerization catalyzed by catalysts I-1 to I-6 as main catalysts
[0191]
[0192]
[0193] aPolymerization conditions: the dosage of main catalyst I-1~I-6 is 1μmol, the co-catalyst is MMAO-7, Al / M=500, the polymerization pressure is 1MPa, the polymerization temperature is 80℃, and the polymerization time is 15min; bMolecular weight and molecular weight distribution are measured by GPC; c 13 Measured by CNMR.
[0194] Example 9: Preparation of propylene-based elastomer by catalytic copolymerization of ethylene / propylene / 1-butene
[0195] The polymerization reaction was carried out in a 1000mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was heated to 160°C, vacuumed for 2h, and the system was cooled to 45°C. 200g of propylene, 50g of 1-butene, and the required amount of modified methylaluminoxane (MMAO) were added to the polymerization autoclave in sequence (the final total volume of the solution was 600mL). The temperature in the autoclave was raised to the polymerization temperature of 80°C. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 2.5MPa. The balance was 15min to fully dissolve ethylene to saturation. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (3MPa). The timing was started and the reaction was terminated after 15min of reaction. The temperature was quickly cooled to 60°C, and the reactor was opened after the pressure was released. The reaction mixture was poured into a mixed solution of 2M hydrochloric acid and ethanol with a volume ratio of 1:1. After stirring for 30min, it was filtered and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high-temperature GPC. The comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 7.
[0196] Table 7 Data of ethylene / propylene / 1-butene copolymerization catalyzed by catalysts I-1 to I-6 as main catalysts
[0197]
[0198]
[0199] aPolymerization conditions: the dosage of main catalyst I-1~I-6 is 1μmol, the co-catalyst is MMAO-7, Al / M=500, the polymerization pressure is 3MPa, the polymerization temperature is 80℃, and the polymerization time is 15min; bMolecular weight and molecular weight distribution are measured by GPC; c 13 Measured by CNMR.
[0200] Example 10: Catalytic copolymerization of ethylene / propylene / 1,3-pentadiene
[0201] The polymerization reaction was carried out in a 1000mL stainless steel autoclave. The autoclave equipped with mechanical stirring was heated to 160°C, vacuumed for 2h, and the system was cooled to 45°C. 200g of propylene and 50g of 1,3-pentadiene were added to the autoclave in turn; the required amount of modified methylaluminoxane (MMAO) was added (the final total volume of the solution was 600mL), and the temperature in the autoclave was raised to the polymerization temperature of 80°C. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 2.5MPa, and the balance was performed for 15min to fully dissolve ethylene to saturation. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (3MPa), and the timing was started. The reaction was terminated after 15min of reaction. The temperature was quickly cooled to 60°C, and the reactor was opened after the pressure was released. The reaction mixture was poured into a mixed solution of 2M hydrochloric acid and ethanol with a volume ratio of 1:1, stirred for 30min, filtered, and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high-temperature GPC. The comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 8.
[0202] Table 8 Data of ethylene / propylene / 1,3-pentadiene copolymerization catalyzed by catalysts I-1 to I-6 as main catalysts
[0203]
[0204]
[0205] aPolymerization conditions: the dosage of main catalyst I-1~I-6 is 1μmol, the co-catalyst is MMAO-7, Al / M=500, the polymerization pressure is 3MPa, the polymerization temperature is 80℃, and the polymerization time is 15min; bMolecular weight and molecular weight distribution are measured by GPC; c 13 Measured by CNMR.
[0206] From the above examples, it can be seen that the cyclobridged dicyclopentadiene catalyst developed by the present invention has high thermal stability, high activity, and high copolymerization performance. It can maintain a high catalytic activity at 150°C. This type of catalyst has super high activity in catalyzing the copolymerization of ethylene with 1-butene, 1-hexene, and 1-octene. At the same time, the molecular weight and comonomer insertion rate of the polymer are also very high. The experimental results show that the molecular weight of the polymer obtained by the copolymerization of ethylene and 1-butene catalyzed by the catalyst provided by the present invention is as high as 38.5×10 4 g / mol, the highest molar insertion rate of 1-butene is 36.2%; the molecular weight of the polymer obtained by copolymerization of ethylene and 1-hexene is up to 40.1×10 4 g / mol, the highest molar insertion rate of 1-hexene is 25.1%; the molecular weight of the polymer obtained by copolymerization of ethylene and 1-octene is up to 36.1×104 g / mol, the highest molar insertion rate of 1-octene is 19.0%; the molecular weight of the polymer obtained by copolymerization of ethylene and propylene is up to 25.9×10 4 g / mol, the highest ethylene molar insertion rate is 52.2%; the molecular weight of the polymer obtained by copolymerization of propylene and butene is up to 26.2×10 4 g / mol, the highest butene molar insertion rate is 18.2%; the molecular weight of the polymer obtained by ethylene / propylene / 1-butene copolymerization is up to 27.2×10 4 g / mol, the molar insertion rate of ethylene is 17.0% to 28.2%, the molar insertion rate of propylene is 67.5% to 75.5%, and the molar insertion rate of 1-butene is 4.5% to 7.5%; the molecular weight of the polymer obtained by ethylene / propylene / 1,3-pentadiene copolymerization is as high as 26.5×10 4 g / mol, the molar insertion rate of ethylene is 18.2% to 27.1%, the molar insertion rate of propylene is 67.4% to 75.3%, and the molar insertion rate of 1,3-pentadiene is 3.4% to 6.5%.
[0207] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A cyclic bridged dicyclopentadienyl catalyst having a structure shown in Formula I: in, M is selected from the fourth subgroup transition metal; R1 is selected from halogen, substituted or unsubstituted alkyl, amine, anionic ligand or neutral ligand that can coordinate with a lone electron pair; X is selected from oxygen, sulfur, nitrogen, selenium, and carbon; When X is selected from oxygen, sulfur or selenium, R2 is absent; When X is selected from nitrogen or carbon, R2 is selected from hydrogen, substituted or unsubstituted alkyl, cycloalkyl, aryl, heteroaryl, silicon; R3~R 22 Independently selected from halogen, hydrogen, substituted or unsubstituted alkyl, alkoxy, cycloalkyl, aryl, heteroaryl, silicon; Or the R7-R 10 For any two adjacent 11 -R 14 For any two adjacent 16 -R 19 For any two adjacent 20 , R 21 , R 22 , R 15 Any two adjacent ones of the aryl carbon atoms to which they are connected together form a substituted or unsubstituted five-membered to twelve-membered cyclic structure group.
2. The cyclic bridged diocene catalyst according to claim 1, characterized in that: The M is selected from Zr, Hf or Ti.
3. The cyclic bridged diocene catalyst according to claim 1, characterized in that: The R1 is selected from halogen, substituted or unsubstituted C1-C10 alkyl, amine; The substituents of R1 are independently selected from halogen, alkyl, alkoxy, silicon, aryl, or heteroaryl.
4. The cyclic bridged diocene catalyst according to claim 1, characterized in that: The X is selected from oxygen, sulfur, nitrogen, selenium, and carbon; When X is selected from oxygen or sulfur, R2 is absent; When X is selected from nitrogen, selenium or carbon, R2 is selected from hydrogen, substituted or unsubstituted C1-C10 alkyl, 3-6 membered cycloalkyl, C6-C12 aryl, C2-C12 heteroaryl, silicon; The substituents of R2 are independently selected from halogen, alkyl, alkoxy, aryl or heteroaryl.
5. The cyclic bridged diocene catalyst according to claim 1, characterized in that: R3~R 22 independently selected from halogen, hydrogen, substituted or unsubstituted C1-C10 alkyl, C1-C10 alkoxy, 3-6 membered cycloalkyl, C6-C12 aryl, C2-C12 heteroaryl, silicon; The above R3~R 22 The substituents are independently selected from halogen, alkyl, alkoxy, aryl or heteroaryl; Or the R7-R 10 For any two adjacent 11 -R 14 For any two adjacent 16 -R 19 For any two adjacent 20 , R 21 , R 22 , R 15 Any two adjacent groups in the group, together with the connected aryl group, form a substituted or unsubstituted five-membered to twelve-membered cyclic structure group; The substituent of the cyclic structure group is selected from halogen, alkyl, alkoxy, aryl or heteroaryl.
6. The cyclic bridged diocene catalyst according to claim 1, characterized in that: Has any of the following structures:
7. The method for preparing the cyclic bridged diocene catalyst according to any one of claims 1 to 6, comprising the following steps: S1) reacting the compound represented by formula a with the compound represented by formula b to obtain a compound represented by formula c; S2) the compound represented by formula c undergoes coordination reaction with a metal precursor to obtain a cyclic bridged dicyclopentadienyl catalyst represented by formula I; Among them, M, R1, X, R2, R3~R 22 The scope is as described in any one of claims 1 to 6.
8. A catalyst system for olefin polymerization, comprising at least two of a catalyst, a co-catalyst, and a boron agent; The catalyst is the cyclic bridged diocene catalyst according to any one of claims 1 to 6.
9. The catalyst system for olefin polymerization according to claim 8, characterized in that The co-catalyst is selected from one or more of alkyl aluminum, aluminoxane and alkyl aluminum chloride; The boron agent is selected from tris(pentafluorophenyl)boron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, tris(4-octylphenyl)carbonium tetrakis(pentafluorophenyl)borate, [PhNHMe2][B(C6F5)4], [(C 18 H 37 )2NHMe][B(C6F5)4]、[C 18 H 37 NHMePh][B(C6F5)4] or more.
10. A method for preparing an olefin polymer, characterized in that: include: Under the catalytic action of the cyclic bridged dioctenes catalyst according to any one of claims 1 to 6 or the catalyst system according to any one of claims 8 to 9, one or more olefins are polymerized to prepare olefin polymers; The olefins include one or more of ethylene, propylene, 1-butene, 1-hexene, 1-octene, styrene, cyclopentene, cyclohexene, norbornene, ethylidene norbornene, 1,3-butadiene, and 1,3-pentadiene; The polymerization reaction temperature is 80-200° C., and the polymerization reaction pressure is 0.1-10 MPa. The prepared olefin polymer is characterized in that The molecular weight Mw of the olefin polymer is 100 to 800 kg·mol -1 The molar insertion rate of the olefin monomer is 9 to 40 mol%, the melting point is 20 to 90°C, the glass transition temperature is -40 to -90°C, and the transmittance is ≥91%.
Citation Information
Patent Citations
Crosslinked metallocene compound for polymerizing olefin and method for polymerizing the olefin by using the same
CN1684968A
Fourth subgroup metal complex with rigid annular bridging structure and application of fourth subgroup metal complex
CN113004316A
Silicon-bridged single metallocene complex containing neutral ligand side arm and application of silicon-bridged single metallocene complex
CN118084987A
Metallocene complex and application thereof, preparation method of olefin polymer and ethylene / alpha-olefin copolymer
CN118459511A
Olefin polymerization catalyst and production of polyolefin using the same
JP1997110919A